A experiência com a utilização do pregão eletrônico nas aquisições de bens: o caso das unidades gestoras do Exército brasileiro sediadas no Estado do Rio de Janeiro - Paz, Sinderley Junior Ferreira (2016)
This study had as its central objective to identify the experience gained with the use of electronic trading on the acquisition of assets from Brazilian Army Management Units based in the state of Rio de Janeiro. For that, we considered the contracting of materials made by about 40 management units in 2015 in different bidding modalities. Another point raised is related to how the developed countries carry out their public procurement and to what extent, these routines can assist in improving the routine adopted by the Federal Public Administration in carrying out their contracts. Statistical analyzes were performed on the extracted data base Management System Treasury regarding the signings made in 2015 in order to point out opportunities for improvement and to ratify if the Management Units are following the existing requirements for achieving efficient public procurement. The study results indicate that the public managers of these Management Units are predominantly using electronic auctions for the purchase of common goods and services, however, not everyone is having the same success in using the tool. As for the amounts paid by the Management Units in certain items, the survey shows considerable variation in the prices thereby damaging an economy of scale and reducing efficiency in the hirings.